IIT JEE 1983 - 'Adapted' - Subjective to Multi-Correct Q3

Algebra Level 4

If ( 1 + x ) n = C 0 + C 1 x + C 2 x 2 + . . . + C n x n \displaystyle (1+x)^n=C_0+C_1x+C_2x^2+...+C_nx^n , then the sum of the products of the coefficients taken two at a time can be represented by i = 0 n j = i + 1 n C i C j = 2 a b ! c ( d ! ) 2 \sum_{i=0}^n \sum_{j=i+1}^{n}C_iC_j = 2^a - \frac{b!}{c(d!)^2} Then which of the following are correct?

  • A: a = 2 n 1 \ a=2n-1
  • B: b = 2 n \ b=2n
  • C: c = 2 \ c=2
  • D: d = n \ d=n

Enter your answer as a 4-digit string of 1s and 9s - 1 for correct option, 9 for wrong. For example, 1199 indicates A and B are correct, C and D are incorrect. None, one or all may also be correct.


In case you are preparing for IIT JEE, you may want to try IIT JEE 1983 Mathematics Archives .


The answer is 1111.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Jan 17, 2017

We note that the coefficient C k C_k is binomial coefficient ( n k ) \displaystyle {n \choose k} . Using the identity below:

( i = 0 n C i ) 2 = i = 0 n C i 2 + 2 i = 0 n j = i + 1 n C i C j i = 0 n j = i + 1 n C i C j = 1 2 [ ( i = 0 n C i ) 2 i = 0 n C i 2 ] = 1 2 [ ( i = 0 n ( n i ) ) 2 i = 0 n ( n i ) 2 ] Vandermonde’s identity: k = 0 r ( m k ) ( n r k ) = ( m + n r ) = 1 2 [ 2 2 n ( 2 n n ) ] = 2 2 n 1 ( 2 n ) ! 2 ( n ! ) 2 \begin{aligned} \left(\sum_{i=0}^n C_i \right)^2 & = \sum_{i=0}^n C_i^2 + 2 \sum_{i=0}^n \sum_{j=i+1}^n C_iC_j \\ \implies \sum _{i=0}^n \sum_{j=i+1}^n C_iC_j & = \frac 12 \left[ \left(\sum_{i=0}^n C_i \right)^2 - \sum_{i=0}^n C_i^2 \right] \\ & = \frac 12 \left[ \left( \sum_{i=0}^n {n \choose i} \right)^2 - {\color{#3D99F6} \sum_{i=0}^n {n \choose i}^2} \right] & \small \color{#3D99F6} \text{Vandermonde's identity: } \sum_{k=0}^r {m \choose k}{n \choose r-k} = {m+n \choose r} \\ & = \frac 12 \left[ 2^{2n} - \color{#3D99F6} {2n \choose n} \right] \\ & = 2^{2n-1} - \frac {(2n)!}{2(n!)^2} \end{aligned}

Therefore,

  • A: a = 2 n 1 \ a = 2n - 1 true
  • B: b = 2 n \ b = 2n true
  • C: c = 2 \ c = 2 true
  • D: d = n \ d = n true

And the answer is 1111 \boxed{1111} .


Reference: Vandermonde's identity

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...